2019
DOI: 10.1080/09540105.2019.1608160
|View full text |Cite
|
Sign up to set email alerts
|

Development a monoclonal antibody-based enzyme-linked immunosorbent assay for screening pyrimethanil in fruits and vegetables

Abstract: Abuse of pyrimethanil in crops to cause deleterious effects on humans has been of great concern. In this study, functionalized derivatives of pyrimethanil have been synthesized and conjugated to carrier proteins, and highly specific and sensitive monoclonal antibodies (mAb) have been produced. Based on the mAb 1F05, an ic-ELISA was developed and characterized for the analysis of pyrimethanil residues. The standard curves based on the pyrimethanil matrix calibration ranged from 0.03 to 3 ng/mL, with a 50% inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…In this article, we chose cucumber and tomato as our test samples, and the samples were pretreated as follows (Cao et al, 2019). Briefly, cucumber and tomato were shred and homogenized first, 5 g of homogenized sample were weighed into a 50 ml polystyrene centrifuge tube, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we chose cucumber and tomato as our test samples, and the samples were pretreated as follows (Cao et al, 2019). Briefly, cucumber and tomato were shred and homogenized first, 5 g of homogenized sample were weighed into a 50 ml polystyrene centrifuge tube, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These include high performance liquid chromatography (Zhou et al, 2011), liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) (Fan, Zhao, Yu, Pan, & Li, 2014; Kasiotis, Anagnostopoulos, Anastasiadou, & Machera, 2014; Tran et al, 2012), gas chromatography (GC) (Łozowicka, 2013), gas chromatography coupled to mass spectrometry in tandem (GC–MS/MS) (Hart, Coscollà, Pastor, & Yusà, 2012; Walorczyk et al, 2013); however, these instrumental methods are time‐consuming and need comprehensive clean‐up steps to ensure efficient extract purification, and the instrumental equipment mentioned above are very expensive and require trained personnel to operate. Immunoassays like ELISA (Cao, Shi, Le, Tang, & Xie, 2019; Esteve‐Turrillas, Mercader, Agulló, Abad‐Somovilla, & Abad‐Fuentes, 2015; Mercader, Esteve‐Turrillas, Agulló, Abad‐Somovilla, & Abad‐Fuentes, 2012), nanogold‐based immunochromatography test strip (Chen et al, 2019; Xie et al, 2020), and newly developed electrochemical sensors, surface enhanced Raman scattering (Mandrile, Giovannozzi, Durbiano, Martra, & Rossi, 2018) have been widely used as substitutes to traditional instrumental methods for the rapid detection of PYR, providing high sensitivity, specificity and less detection time. So far, however, no studies were reported so far concerning the quantum dots (QDs)‐based lateral flow immunochromatography strip (QDs‐LFICS).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies were conducted according to institutional ethical guidelines and approved by the Committee on Animal Welfare of Jiangnan University. Twenty female BALB/C mice were immunized by injecting with CTV-COOH-KLH using the same procedure as described previously (Cao et al, 2019). Antisera was screened using an ic-ELISA with CTV-COOH-BSA immobilizing on plates.…”
Section: Generation Of Mabmentioning
confidence: 99%
“…Goat anti-mouse IgG was obtained from Sino-American Biotechnology Corporation (Luoyang, China). Hapten 6-(3-(4,6dimethylpyrimidin-2-ylamino)phenyl)hexanoic acid (pMm), anti-pyrimethanil monoclonal antibodie (anti-pyrimethanil mAbs), and pMm-BSA were produced in our laboratory (Cao et al, 2019). All other chemicals and organic solvents were of analytical grade or higher.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…These analytical methods are sensitive and accurate, whilst costly equipment, skilled personnel high cost, and unsuitable for on-site detection are their drawbacks. Consequently, rapid immunoassay methods such as ELISA indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) (Cao, Shi, Le, Tang, & Xie, 2019;Chen et al, 2019;Mercader, Esteve-Turrillas, Agullo, Abad-Somovilla, & Abad-Fuentes, 2012) and colloidal gold immunochromatography test strip (ICTS) (Chen et al, 2019) have been widely used for the rapid detection of pyrimethanil residue. These methods and their reported detection sensitivities are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%